MSCs and Inflammatory Cells Crosstalk in Regenerative Medicine: Concerted Actions for Optimized Resolution Driven by Energy Metabolism - Planat-Benard, Valerie; Varin, Audrey; Casteilla, Louis (Frontiers in Immunology, 2021)
Mesenchymal stromal cells (MSCs) are currently widely used in cell based therapy regarding to their remarkable efficacy in controlling the inflammatory status in patients. Despite recent progress and encouraging results, inconstant therapeutic benefits are reported suggesting that significant breakthroughs in the understanding of MSCs immunomodulatory mechanisms of action remains to be investigated and certainly apprehended from original point of view. This review will focus on the recent findings regarding MSCs close relationship with the innate immune compartment, i.e. granulocytes and myeloid cells. The review will also considerate the intercellular mechanism of communication involved, such as factor secretion, cell-cell contact, extracellular vesicles, mitochondria transfer and efferocytosis. Immune-like-properties of MSCs supporting part of their therapeutic effect in the clinical setting will be discussed, as well as their potentials (immunomodulatory, anti-bacterial, anti-inflammatory, anti-oxidant defenses and metabolic adaptation…) and effects mediated, such as cell polarization, differentiation, death and survival on various immune and tissue cell targets determinant in triggering tissue regeneration. Their metabolic properties in term of sensing, reacting and producing metabolites influencing tissue inflammation will be highlighted. The review will finally open to discussion how ongoing scientific advances on MSCS could be efficiently translated to clinic in chronic and age-related inflammatory diseases and the current limits and gaps that remain to be overcome to achieving tissue regeneration and rejuvenation.